Root Canal Morphology of Mandibular Primary Molars: A Micro-CT Study - Şaziye Sarı; Burcu Nihan Yüksel; Meryem Ziya (Cumhuriyet University, 2019)
Objectives: Frequency of typical and non-typical root and canal morphology of primary teeth, which in clinical practice cannot be detected using 2D radiographic images, should be known by clinicians to decrease failures arising from complexity of root canal morphologies. The aim of this in vitro study was to evaluate morphologic variations in mandibular primary molars' root canal systems. Materials and Methods: Primary mandibular 1st (n=17) and 2nd (n=33) molars were scanned using micro-CT. 3D root models were obtained and root canal morphologies were evaluated according to a modified Vertucci classification. Type 1 and Type 4 canal morphologies were evaluated as 'normal' and all other types and 'non-typical' canal morphology were evaluated as 'abnormal' root canal morphology. Results: Most common root canal morphology among mandibular primary 1st molars were Vertucci Type 4 morphology for both mesial and distal roots (47% and 41.2% respectively), and non-typical morphology for both the mesial and distal roots (45.7% and 21.2% respectively) of mandibular primary 2nd molars. Conclusions: Wide range of morphologic variations and frequency of non-typical morphology could be seen especially among mandibular primary 2nd molars and use of disinfectant irrigants and root canal fillings with high antibacterial efficacies are important in order to decrease failures arising from these inaccessible areas.